Kompetensi kepribadian dan sosial guru dalam menerapkan sikap disiplin peserta didik kelas I pada pembelajaran PPKn di Sekolah Dasar - Detria Nur Aini Sutrisno; Dwi Yuniasih Saputri; Hasan Mahfud (Didaktika Dwija Indria, 2021)
Abstract. This research was conducted to describe teacher’s personal and social competences applying disciplinary attitudes in civic education learning for grade I SD Negeri Tegalrejo No. 98 Academic Year 2020/2021. These research belongs to qualitative research with descriptive qualitative methodes and a case study approach. Teachers and students of class I SD Negeri Tegalrejo No. 98, totaling 14 students, became the research subjects. Data collection techniques using observation, interviews and documentation. The data analysis technique of this research is based on the interactive analysis technique of Miles and Huberman through data collection, data reduction, data presentation and drawing conclusions. Data validity by triangulating techniques and sources. The result showed that the disciplinary attitude of the students was quite good, but there were still some obstacles in its implementation. Indicators of collecting assignments directly in schools have not been fulfilled and there are still network constraints during the implementation of learning. Based on the research results, it can be said that the appplication of a disciplined attitude needs to be instilled from an early age.Keywords: personality and social teacher competency, discipline, elementary school, civic education learning.